2021
DOI: 10.1111/cas.14740
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer–secreted exosomal X26nt increases angiogenesis and vascular permeability by targeting VE‐cadherin

Abstract: Angiogenesis is closely associated with tumorigenesis, invasion, and metastasis by providing oxygen and nutrients. Recently, increasing evidence indicates that cancer‐derived exosomes which contain proteins, coding, and noncoding RNAs (ncRNAs) were shown to have proangiogenic function in cancer. A 26‐nt‐long ncRNA (X26nt) is generated in the process of inositol‐requiring enzyme 1 alpha (IRE1α)‐induced unspliced XBP1 splicing. However, the role of X26nt in the angiogenesis of gastric cancer (GC) remains largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“…has depicted a pro-tumor role of GC cells-released exo, which could augment expansion of myeloid-derived suppressor cells through a transfer of miR-107 [ 34 ]. GC cells-derived exo activates HUVECs to proliferate, migrate and form tubes, and such effects are enhanced via transfer of 26-nt-long ncRNA [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…has depicted a pro-tumor role of GC cells-released exo, which could augment expansion of myeloid-derived suppressor cells through a transfer of miR-107 [ 34 ]. GC cells-derived exo activates HUVECs to proliferate, migrate and form tubes, and such effects are enhanced via transfer of 26-nt-long ncRNA [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that exosomes secreted from cancer cells could be transported to HUVECs. 19 Therefore, we next investigate whether exosomes secreted from ovarian cancer cells could be transported to HUVECs. As showed in Figure 2D and E , PKH26 labeled exosomes were absorbed by HUVECs in a time dependent manner, and these phenomena were notably reversed in the presence of nystatin or heparin.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular endothelial cadherin (VE-cadherin) has been shown to enhance vascular permeability, angiogenesis and tumor growth ( Viallard and Larrivée, 2017 ). The exosomal 26‐nt‐long ncRNA (X26 nt) secreted by GCs can target VE-cadherin to increase angiogenesis and vascular permeability ( Chen et al, 2021a ). The long-chain non-coding RNA MALAT1 was shown to enhance the expression of classic markers such as VE-cadherin and components of related signaling pathways to promote blood vessel growth and angiogenesis ( Li et al, 2017a ).…”
Section: Mechanisms Of Ncrnas That Regulate Gastric Cancer Behaviormentioning
confidence: 99%